2022
DOI: 10.1111/jdv.18561
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pruritus in multiple sclerosis and clinical correlates

Abstract: Background:To date, little is known about the prevalence of itch in multiple sclerosis (MS) and its characteristics.Objectives: In this cross-sectional study, we assessed the prevalence, intensity and characteristics of chronic pruritus in MS patients and its effect on quality-of-life and association with MS symptoms, clinical signs, comorbidities and MRI findings.Methods: MS patients presenting to an outpatient neurology clinic were asked about their current symptoms. Those who experienced chronic pruritus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Paroxysmal pruritus associated with neuroinflammatory conditions (demyelinating diseases) such as multiple sclerosis and neuromyelitis optica is clinically an acute onset and recalcitrant pruritus that is usually triggered by the onset of movement and has frequent attacks during the day. It has been theorized that transversely diffused ephatic activation of partially demyelinating pain-transmitting neurons causes paroxysmal pruritus [51][52][53]. In the study of Ingrasci et al, pruritus was reported in 35% of a total of 77 multiple sclerosis patients.…”
Section: Disorders Affecting the Central Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Paroxysmal pruritus associated with neuroinflammatory conditions (demyelinating diseases) such as multiple sclerosis and neuromyelitis optica is clinically an acute onset and recalcitrant pruritus that is usually triggered by the onset of movement and has frequent attacks during the day. It has been theorized that transversely diffused ephatic activation of partially demyelinating pain-transmitting neurons causes paroxysmal pruritus [51][52][53]. In the study of Ingrasci et al, pruritus was reported in 35% of a total of 77 multiple sclerosis patients.…”
Section: Disorders Affecting the Central Nervous Systemmentioning
confidence: 99%
“…As a result, paroxysmal NP localized to the extremities, face or scalp, most frequently, is seen in multiple sclerosis patients. Patients with pruritus are more likely to have multiple sclerosis-related comorbidities and demyelinating lesions in the spinal cord or brainstem [51]. Muto et al have suggested that most of the opticospinal form of multiple sclerosis is neuromyelitis optica, and it was found that paroxysmal pruritus was more prominent in these cases [52].…”
Section: Disorders Affecting the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Central nerve and peripheral nerve damage secondary to illness, syndromes, or surgery can also elucidate pruritus [21] . Common examples include poststroke, postherpetic, or postsurgical pruritus and multiple sclerosis [22][23][24][25] .…”
Section: Definitionmentioning
confidence: 99%